Dive Behavior and Activity Patterns of Fin Whales in a Migratory Habitat - Catarina T. Fonseca; Sergi Pérez-Jorge; Rui Prieto; Cláudia Oliveira; Marta Tobeña; Annette Scheffer; Annette Scheffer; Mónica A. Silva (Frontiers in Marine Science, 2022)
Efficient use of the energy budget is of fundamental importance for long-distance migrants, which must cope with seasonal energy demands and environmental conditions. Time-activity budgets can provide information on how animals balance energy use and acquisition over their annual cycle, and on the costs and benefits of different migratory strategies. Baleen whales, such as the fin whale, perform long migrations between feeding and breeding grounds. Although there are now a handful of studies describing the diving and foraging behavior of fin whales, most were carried out at their high-latitude foraging grounds, and very little is known about their behavior in wintering habitats or during migration. We analyzed time-depth recorder data to describe the diving behavior and activity patterns of fin whales in a migratory habitat. Using a hierarchical cluster analysis based on a set of dive variables, we identified six dive types. Four of these dive types (shallow exploratory, shallow active, deep exploratory and deep active) were likely associated to foraging. The other two comprised long non-active dives and dives of variable shape, which may represent resting, traveling or even vocalizing behavior. Shallow exploratory dives were the most frequent dive type (23%) and shallow active were the least frequent (5%). The two deepest dive types, deep active and exploratory, were predominantly carried out during the day, and night dives were significantly shallower than daylight dives, suggesting that fin whales tracked the vertical migration of prey. Whales spent 60% of their dive time engaged in dives associated with feeding and/or prey searching, suggesting they prioritized energy intake over energy conservation. Finally, we found that whales spent more time at or close (<15 m depth) to the surface at night (73%) than during the day (55%), indicating a higher vulnerability to ship strikes during this period. Our study provides novel information on the behavioral patterns and time-activity budgets of fin whales in a migratory habitat. This information is essential for bioenergetic analyses and to predict how fin whales respond to human activities and ongoing environmental changes.